Multi-Functional Carbon Dots from an Ayurvedic Medicinal Plant for Cancer Cell Bioimaging Applications - Naik G.G.; Alam M.B.; Pandey V.; Mohapatra D.; Dubey P.K.; Parmar A.S.; Sahu A.N. (My University, 2025)
The combination of an Ayurvedic wisdom and nanotechnology may help us to resolve the complex healthcare challenges. A facile and economical one-pot hydrothermal synthesis method has been adopted for preparing a blue fluorescent carbon dots (CDs) with a quantum yield of 15.10% from an Ayurvedic medicinal plant Andrographis paniculata (AP). The Andrographis paniculata derived CDs (AAPCDs) were then characterized using different techniques. Through High Performance Thin Layer Chromatography (HPTLC) profiling of the AP extract and the CDs, it was found that some of the phytoconstituents are retained as such while others may have been converted into their derivatives during the process of formation of CDs. The CDs are designed to possess cellular imaging of human breast carcinoma cells (MCF-7), apart from free radicals sensing and scavenging capabilities. AAPCDs showed minimal cytotoxicity in Multi Drug Resistant clinically isolated strains of gram positive and gram negative bacteria which may be employed for microbiology oriented experiments. These results suggest potential of multi-functional AAPCDs as nano-probes for various pharmaceutical, biomedical and bioengineering applications. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.